Merancang Sistem Informasi Pariwisata Berbasis Web sebagai Metode Pembelajaran di Kalangan Mahasiswa Perhotelan Udinus - Dedi Joko Purnomo (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
Tourism in Indonesia has grown to become one of the important sectors in increasing the country's foreign exchange earnings. The increase in tourist visit targets proclaimed by the Ministry of Tourism is as many as 20 million tourist visits in 2019 requiring the tourism sector to improve and improve all facilities and infrastructure that can accommodate tourist visits.Tourism information in Indonesia is presented in a web-based data communication model. The web-based communication model with XML format certainly facilitates the complete data transfer. The XML format is more easily adapt to different technologies for each source of data has been collected so that all stakeholders in the tourism industry would easily fit on a system that has been made before, so that will further enhance the advancement of the tourism industry in Indonesia. The ease of transacting information and data is due to using web service technology where this web service technology is a collaboration between a very good data management system without any problems between internal systems in each user. Web service technology was chosen because of the ease in exchanging information and communication between systems that currently use internet media with good security through data encryption. Information Systems in Indonesia currently use web services so as to provide information, data and transaction services in the tourism industry in Indonesia. So designing tourism web service is one of the learning methods taught to hospitality students of Dian Nuswantoro University Semarang.